2004
DOI: 10.2320/matertrans.45.1339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Substitutions of Rare-earth Metals for Na-site on the Thermoelectric Properties of Na<SUB><i>x</i></SUB>Co<SUB>2</SUB>O<SUB>4</SUB> Prepared by the Polymerized Complex Method

Abstract: Polycrystalline (Na 1Ày M y ) x Co 2 O 4 (M=Nd, Sm, Dy and Yb; y ¼ 0:01 $ 0:05) samples were synthesized by a polymerized complex method. The effects of partial substitution of rare-earth metals for a Na-site on the thermoelectric properties of Na x Co 2 O 4 were investigated, and their differences with the sample prepared by a conventional solid-state reaction (SSR) method were evaluated. In case of the Nd, Sm and Dysubstituted samples, each rare-earth metal content in the matrix phase was slightly higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…The data are taken from the following works: K [5], Mn [10], Ni [17]. Cu [14], Zn [16,18], Sr and Y [5], Ru [10], Ag [12,15], Nd [5], Sm [5,11], Dy [11], Yb [5,11], Au [15]. Cu doping, the most stable configuration was Y Co with a formation energy of 3.94 eV for x = 0.75 and 3.74 eV for x = 1.00.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data are taken from the following works: K [5], Mn [10], Ni [17]. Cu [14], Zn [16,18], Sr and Y [5], Ru [10], Ag [12,15], Nd [5], Sm [5,11], Dy [11], Yb [5,11], Au [15]. Cu doping, the most stable configuration was Y Co with a formation energy of 3.94 eV for x = 0.75 and 3.74 eV for x = 1.00.…”
Section: Resultsmentioning
confidence: 99%
“…21 Real-space global cut-off radii were set for all elements at 6. The data are taken from the following works: K, 5 Mn, 10 Ni, 17 Cu, 14 Zn, 16,18 Sr and Y, 5 Ru, 10 Ag, 12,15 Nd, 5 Sm, 5,11 Dy, 11 Yb, 5,11 and Au. 15 found that the interstitial dopants are more stable when located on a vacant Na2 (or Wyckoff d) position.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of the efforts, doping Na x CoO 2 , as a strategy to enhance the thermoelectric performance, delivered mixed results. For instance, heavier ions such as rare earth Yb and noble metal Ag were successfully used to decrease the lattice thermal conductivity (k l ) and thus improving ZT [17,18]. Doping Ru and Mn in Na 0.5 CoO 2 , however, increased the resistivity to ~ 300 µΩ m, three times higher than that of the undoped Na 0.5 CoO 2 [19].…”
Section: Introductionmentioning
confidence: 99%